THE IMPACT OF GENDER DIFFERENCES IN TEACHER–STUDENT RELATIONSHIPS ON EDUCATION QUALITY AND PERSONAL DEVELOPMENT - Nigar Huseynova Chingiz, (International Journal of Innovative Technologies in Social Science, 2025)
This study explores the influence of gender differences in teacher–student relationships on the quality of education and learners’ personal development. Contemporary education extends beyond the transmission of knowledge and is shaped by social interaction, communication patterns, and pedagogical styles. Teachers’ expectations, communication approaches, and instructional decisions are often—consciously or unconsciously—influenced by gender-based assumptions. These factors affect students’ motivation, self-confidence, academic performance, and social adaptation. The theoretical framework draws on constructivism, Bloom’s Taxonomy, transformative learning theory, and the principles of gender pedagogy. The methodology includes classroom observations, a survey of 120 students, interviews with 20 teachers, and a literature review. The findings show that in gender-sensitive learning environments, student motivation increased by 20–25%, academic performance improved by 10–12%, and self-confidence indicators rose significantly. The study concludes that gender equality in teacher–student interactions is essential for enhancing educational quality. It recommends teacher training in gender-sensitive pedagogy, the adoption of gender-neutral assessment criteria, and the creation of inclusive learning environments.